Alteration of Intestinal Microbiota Composition in Oral Sensitized C3H/HeJ Mice Is Associated With Changes in Dendritic Cells and T Cells in Mesenteric Lymph Nodes - Zhou, Cui; Chen, Ling-Ling; Lu, Rui-Qi; Ma, Wei-Wei; Xiao, Rong (Frontiers in Immunology, 2021)
This research aimed to investigate the allergic reaction of C3H/HeJ mice after sensitisation with ovalbumin (OVA) without any adjuvant, and to analyze the association between intestinal microbiota and allergy-related immune cells in mesenteric lymph nodes (MLN). Allergic responses of C3H/HeJ mice orally sensitized with OVA were evaluated, immune cell subsets in spleen and MLN and cytokines were also detected. The intestinal bacterial community structure was analyzed, followed by Spearman correlation analysis between changed gut microbiota species and allergic parameters. Sensitization induced noticeable allergic response to the gavage of OVA without adjuvant. Increased levels of Th2, IL-4, CD103+CD86+ DC, and MHCⅡ+CD86+ DC, and decreased levels of Th1, Treg, IFN-γ, TGF-β1, and CD11C+CD103+ DC were observed in allergic mice. Furthermore, families of Lachnospiraceae, Clostridiaceae_1, Ruminococcaceae, and peprostreptococcaceae, all of which belonging to order of Clostridiales, were positively related to Treg and CD11C+CD103+ DC, while negatively related to allergic reaction, levels of Th2, CD103+CD86+ DC and MHCⅡ+CD86+ DC in MLN. The family of norank_o_Mollicutes_RF39 belonging to order of Mollicutes_RF39 was similarly correlated with allergic reaction and immune cells in MLN of mice. To sum up, allergic reactions and intestinal flora disturbances could be induced by OVA oral administration alone. The orders of Clostridiales and Mollicutes_RF39 in intestinal flora are positively correlated with levels of Treg and CD11C+CD103+ DC in MLN of mice.